Microbial metabolites and their influence on the tumor microenvironment - Duan, Huanglin; Xu, Baisheng; Luo, Peiyue; Chen, Tao; Zou, Jun (Frontiers in Immunology, 2025)
While tumor immunotherapy has achieved remarkable progress in many hematological malignancies, its efficacy remains limited by key challenges, including the immunosuppressive microenvironment of solid tumors, metabolic abnormalities, and drug resistance. As a central mechanism underlying impaired immune function, metabolic reprogramming of immune cells has emerged as a pivotal focus for unraveling tumor immune evasion and therapeutic resistance. Advances in metagenomics have highlighted the significance of the human commensal microbiome as a ‘second genome.’ Microbial metabolites, whether circulating systemically or accumulating locally, serve as key messengers linking the microbiota to tumor immunometabolism. This review comprehensively examines the regulatory roles and metabolic mechanisms through which microbial metabolites—including short-chain fatty acids (SCFAs), bile acids, tryptophan metabolites, and lipopolysaccharides (LPS)—modulate tumor immunity and immunotherapeutic responses via immune cell metabolism. These metabolites shape the tumor immune microenvironment and influence immunotherapeutic efficacy by reprogramming immune cell metabolic and biosynthetic pathways. This review underscores the central regulatory role of microbial metabolites as the ‘second genome’ in tumor immunometabolism, offering a theoretical foundation and potential targets to elucidate mechanisms of immunotherapeutic resistance and advance microbiota metabolism-based precision interventions.